Associations of dyslipidaemia and lipid-lowering treatment with risk of postoperative cognitive dysfunction: a systematic review and meta-analysis. Issue 6 (2nd February 2018) - Feinkohl, Insa; Winterer, Georg; Pischon, Tobias
Abstract : Background: Lipid imbalance is linked to age-related cognitive impairment, but its role in postoperative cognitive dysfunction (POCD) is unknown. Here, we present a systematic review and meta-analysis on dyslipidaemia, lipid-lowering treatment and POCD risk. Methods: PubMed, Ovid SP and Cochrane databases were searched for longitudinal studies that reported on associations of any measure of dyslipidaemia and/or lipid-lowering treatment with POCD as relative risks (RRs) or ORs. Fixed-effects inverse variance models were used to combine effects. Results: Of 205 articles identified in the search, 17 studies on 2725 patients (grand mean age 67 years; mean age range 61–71 years) with follow-up periods of 1 day to 4 years (median 7 days; IQR 1–68 days) were included. Studies focused almost exclusively on hypercholesterolaemia as a measure of dyslipidaemia and on statins as lipid-lowering treatment. Across 12 studies on hypercholesterolaemia, we found no association with POCD risk (RR 0.93; 95% CI 0.80 to 1.08; P=0.34). Statin use before surgery was associated with a reduced POCD risk across eight studies (RR 0.81; 95% CI 0.67 to 0.98; P=0.03), but data on treatment duration were lacking. Conclusion: Statin users appear to be at reduced risk of POCD although hypercholesterolaemia per se may not be associated with POCD risk. Trial studies are needed to evaluate the usefulness of statins in POCD prevention.